2005
DOI: 10.1159/000088072
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of a Combination of S-1 and Weekly Paclitaxel in Patients with Advanced or Recurrent Gastric Cancer

Abstract: Objective: A phase I study of weekly intravenous paclitaxel combined with a fixed dose of S-1, a dihydropyrimidine-dehydrogenase-inhibitory oral fluoropyrimidine, was conducted for patients with advanced or recurrent gastric cancer (ARGC). Endpoints of this study were to examine the toxicity profile of this regimen and to determine the recommended dose (RD) of paclitaxel. Methods: S-1 was fixed at a dose of 80 mg/m2 per day and was administered for 2 weeks (days 1–14) followed by a 2-week rest. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…The gastrointestinal toxicities of the current regimen were tolerable, with less than 5% of cases with grade 3 diarrhea and stomatitis. In the Japanese phase I/II trial, reported by Ueda et al [23], febrile neutropenia developed in one (17%) patient with 40.0 mg/m 2 per week of paclitaxel and in one (11%) patient with 33.3 mg/ m 2 per week of paclitaxel . In the current study, febrile neutropenia developed in four (7%) patients with 46.7 mg/m 2 per week of paclitaxel.…”
Section: Time (Weeks)mentioning
confidence: 94%
See 2 more Smart Citations
“…The gastrointestinal toxicities of the current regimen were tolerable, with less than 5% of cases with grade 3 diarrhea and stomatitis. In the Japanese phase I/II trial, reported by Ueda et al [23], febrile neutropenia developed in one (17%) patient with 40.0 mg/m 2 per week of paclitaxel and in one (11%) patient with 33.3 mg/ m 2 per week of paclitaxel . In the current study, febrile neutropenia developed in four (7%) patients with 46.7 mg/m 2 per week of paclitaxel.…”
Section: Time (Weeks)mentioning
confidence: 94%
“…In Korean trial, the dose was Wnely adjusted compared with Japanese trials in which S-1 dose by body surface area (BSA) was roughly divided into three levels. The actual dose was nearly same in patients with BSA between 1.4-1.7 m 2 of two nations paclitaxel 50-60 mg/m 2 , weekly [6,7,9,13,17,20,23]. The most common dose limiting toxicities were grade 3 diarrhea or grade 4 neutropenia.…”
Section: Time (Weeks)mentioning
confidence: 95%
See 1 more Smart Citation
“…The response rate has been reported to be 40%-60% with the schedule of S-1 80 mg/m 2 for 14 days plus paclitaxel 50-60 mg/m 2 on days 1 and 8 or days 1 and 15. We have also conducted a phase I clinical trial of 2 weeks S-1 plus weekly paclitaxel on days 1, 8, and 15 of a 4-week cycle [34]. Based on the data from that trial, a multicenter phase II study was conducted by the Kyoto Gastrointestinal Cancer Chemotherapy Study Group in order to assess the effi cacy of S-1 and weekly paclitaxel administered every 4 weeks as fi rstline treatment for patients with advanced or metastatic gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…At present, clinical studies of TS-1 combined with taxanes or cisplatin in patients with advanced gastric cancer have been evaluated. (9,59,60) It has been reported that docetaxel and S-1 combination therapy are highly active and well tolerated in advanced or recurrent gastric cancer. (57) Capecitabine is an orally administered fluoropyrimidine anticancer drug used in the treatment of metastatic breast and Sakamoto et al reported that the administration of capecitabine for the treatment of chemotherapy-naive patients with unresectable advanced or metastatic gastric cancer showed promising activity and was well tolerated as a first-line therapy for advanced and metastatic gastric cancer.…”
Section: Future Chemotherapy Using Novel Antimetabolitesmentioning
confidence: 99%